The impact of interactive motor-cognitive dual tasking on brain activation, functional connectivity, and behavioral performance in healthy adults: an fNIRS study - Li, Xiaohan; Tang, Lifeng; Zhang, Yuting; Ye, Lin; Zhou, Lifeng; Tang, Min (Frontiers in Human Neuroscience, 2025)
ObjectiveThis study aimed to explore how varying levels of interactive motor-cognitive dual task difficulty affect brain activation, functional connectivity (FC), and behavioral performance in healthy adults using functional near-infrared spectroscopy (fNIRS).MethodsWe recruited 28 healthy participants to perform interactive motor-cognitive dual task at three difficulty levels: easy task (ET), medium task (MT), and difficult task (DT). The tasks involved walking while simultaneously engaging in cognitive challenges. A continuous-wave fNIRS system was used to collect fNIRS data during the task, focusing on 10 regions of interest (ROIs): left/right prefrontal cortex (LPFC/RPFC), left/right dorsolateral prefrontal cortex (DLPFC/DRPFC), left/right premotor cortex (LPMC/RPMC), left/right sensorimotor cortex (LSC/RSC), and left/right motor cortex (LMC/RMC). Simultaneously, the subjects’ gait data during walking were collected using an Inertial Measurement Unit (IMU) sensor, and their cognitive performance was recorded by the researchers.ResultsStatistical analysis revealed statistically significant differences in the mean HbO levels among the three groups for the DRPFC, LPMC/RPMC, RSC, and LMC/RMC regions. Additionally, significant differences were found in the activation of channels 3, 18, 24, 25, 28, and 29 across the three groups. The group-averaged FC in the DT (0.61 ± 0.21) was significantly higher than that in the ET (0.46 ± 0.21, P = 0.023). ROI-to-ROI FC analysis showed significant differences among the three groups in the LSC∼RPMC, RPMC∼RSC, and RSC∼RMC connections. The lateralization index (LI) ranged from 0.10 to 0.35, indicating a predominant right-brain lateralization during the interactive motor-cognitive dual task. Additionally, compared to the MT, both speed and stride length, as well as cognitive performance, were lower during the DT.ConclusionWe found that increased task difficulty heightened activation in the premotor and motor cortices, with a tendency toward right hemisphere dominance. Higher task difficulty also strengthened FC, particularly in motor-related regions, indicating greater neural coordination. Behaviorally, participants exhibited slower gait parameters and reduced cognitive performance as task complexity increased, highlighting the impact of dual-task interference.